Effect of Temperature on The Electron Concentration of Crystalline GaAs Semiconductor Based on The p-n Junction Due to Deformation Potential Scattering - Alviati, Nova; Hoiriyah, Samsiatun; Misto, Misto; Supriyanto, Edy (Physics Department, Faculty of Mathematics and Natural Sciences, University of Jember, 2019)
The electrical characteristics of semiconductor materials can be predicted based on the transport of charge carriers within the material. Under room temperature, the electrical properties of semiconductor materials can be exploited by knowing the value of their electron mobility to predict the number of electrons that experience the transport mechanism. When the material is observed under room temperature, the interaction of electrons and the lattice atoms' vibrations result in deformation potential scattering. This can stimulate electron mobility changes, which can affect the number of free electrons in semiconductor materials. The research results presented in this paper simulate the number of electrons that change due to electrons' mobility in the GaAs crystal. This material undergoes potential scattering deformation due to the interaction between electrons and phonons at temperature (40-100) K. The simulation is carried out by modeling the GaAs semiconductor material in the form of a p-n junction. The temperature variation given to the material shows a significant change in concentration in the junction area. In contrast, in the contact area's vicinity with the external circuit, both the p-layer and the n-layer show relatively constant electron concentrations.